2018
DOI: 10.1097/icb.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Recessive Bestrophinopathy: Multimodal Imaging Update

Abstract: We describe modern multimodal imaging in an individual with a BEST1 gene mutation and clinical findings consistent with an autosomal recessive bestrophinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The phenotype additionally encompasses extramacular punctate deposits, intraretinal and subretinal fluid (SRF) accumulation, punctate or diffuse fundus hyperautofluorescence, hyperopia, short axial-length, central visual field loss, severely decreased Arden ratio (≤1.0) on EOG, and reduced photopic and scotopic ffERG. [10][11][12] Amblyopia and angle closure glaucoma can co-occur. 12,13 As such, VMD and ARB macular phenotypes may overlap depending on the stage, distinguishable by the typically normal ffERG in VMD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype additionally encompasses extramacular punctate deposits, intraretinal and subretinal fluid (SRF) accumulation, punctate or diffuse fundus hyperautofluorescence, hyperopia, short axial-length, central visual field loss, severely decreased Arden ratio (≤1.0) on EOG, and reduced photopic and scotopic ffERG. [10][11][12] Amblyopia and angle closure glaucoma can co-occur. 12,13 As such, VMD and ARB macular phenotypes may overlap depending on the stage, distinguishable by the typically normal ffERG in VMD.…”
mentioning
confidence: 99%
“…[10][11][12] Amblyopia and angle closure glaucoma can co-occur. 12,13 As such, VMD and ARB macular phenotypes may overlap depending on the stage, distinguishable by the typically normal ffERG in VMD. Both phenotypes display a propensity for SRF accumulation, RPE-photoreceptor separation, disruption of photoreceptor outer segment shedding 11 and lipofuscin-like deposits between the neurosensory retina and RPE.…”
mentioning
confidence: 99%
“…The eleven patients reported in this study display key clinical features of the condition, including loss of central vision in early life, angle-closure glaucoma, subretinal and intraretinal fluid accumulation, macular and peripheral vitelliform lesions with yellow flecks but without autofluorescent yellow vitelliform lesions covering the whole macula like in vitelliform macular dystrophy, a lack of dominant mode of inheritance and abnormal electrophysiology (ERG and EOG light rise) The phenotype of our patients were compared to other publications ( Table 2). Multimodal imaging can be helpful in better visualizing retinal abnormalities; OCT allows for easy identification of macular lesions, including hyperreflective accumulations on RPE, cystoid intra-retinal and serous subretinal fluid, and wide-field fundus autofluorescence helps to localize retinal abnormalities by revealing autofluorescent material [16].…”
Section: Discussionmentioning
confidence: 99%
“…At that time, there were also no fundus autofluorescence and EOG results, and the onset age was young. The typical clinical findings in patients with ARB often manifest as multifocal subretinal vitelliform deposits, diffuse SRF, and remarkable abnormalities on autofluorescence imaging ( Kalevar et al, 2018 ), while it has not been reported that retinoschisis was present in any ARB patient before 2012 ( Preising et al, 2012 ). In recent literature, ARB cases showed retinoschisis, macular cystic changes, and MNV ( Khojasteh et al, 2021 ), which might be a possible pathogenic role of choroid in different stages of the disease ( Grenga et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Burgess et al (2008) first designated the constellation of findings in 2008 now known as ARB. High hyperopia, shallow anterior segment, angle-closure glaucoma, abnormal electroretinogram (EOG), intraretinal cystic changes, and concurrent subretinal fluid have been reported in ARB patients ( Kalevar et al, 2018 ). Here, we report a patient who presented with retinoschisis and cystic changes in childhood and was identified as an individual with BEST1 gene mutation 13 years later, and the clinical findings were consistent with ARB.…”
Section: Introductionmentioning
confidence: 99%